Computer Graphics : Principles and practice - Hughes, John F.; Van Dam, Andries; Mcguire, Morgan (New Jersey Pearson Education, Inc., 2014)
Contents: Introduction to 2D graphics using WPF; an ancient renderer made modern; a 2D graphics test bed; an introduction to human visual perception;...
Includes bibliographical references and index
Keywords: Công nghệ thông tin